Role of socioeconomy and land management in the evolution of agrosilvopastoral landscapes in Northern Spain: The case study of Redes Biosphere Reserve - González Díaz, José Antonio; González Díaz, Benjamín; Rosa-García, Rocío (Frontiers in Ecology and Evolution, 2022)
Agrosilvopastoral systems are multifunctional, complex and knowledge intensive systems with potential to deliver multiple ecosystem services. However, their future is hindered by socio-ecological factors which influence the dynamics of the associated landscapes by modifying how the natural resources are used over time and across the territory. An integrated analysis of the most influential factors and the associated dynamics urges due to the strategic potential of these systems to provide locally adapted ecosystem services to face both local and global challenges. We investigated the changes of the demography, productive activities and the strategies of land use, and how they influenced the landscape dynamics, in the Redes Biosphere Reserve. Datasets with demographic, socioeconomic and landscape parameters from 1956, 1985 and 2016 were created. Landscape metrics were calculated for the whole Reserve and for six areas covering the bioclimatic variability. Historical data, interviews with the local population and repeated images were used to reconstruct the land uses and the landscape maps in each period. The number of inhabitants declined 60% from 1956 to 2016, only 4.7% are less than 15 years old nowadays. The human group's capacity to maintain sustainable and productive activities is highly questionable. During the same period the number of farms decreased 80% and the herds evolved from multispecific (63% cattle and 37% small ruminants) to monospecific ones (around 88% cattle). The complex land management strategies simplified: subsistence agriculture almost disappeared and the diversity of livestock and agroforestry strategies also decreased. The landscape metrics revealed the most drastic changes in the lowlands associated with the construction of two water reservoirs and the disappearance of croplands and open chestnut forests. At middle altitudes around 43% of the hay meadows disappeared and the remaining grasslands are only grazed, whereas grazed grasslands declined 77% at the highest altitudes. Two drivers repeated across the three bioclimatic scenarios: expansion of dense woodlands (average 220%) and shrublands (295%). All these changes led to the reduction of the landscape diversity and the simplification of the mosaic, with possible environmental implications. Integrated approaches including environmental and socioeconomic measures are needed to preserve the landscapes and associated services.